2018
DOI: 10.1101/456566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread Suppression of High-Order Visual Cortex During Blinks and External Predictable Visual Interruptions

Abstract: Spontaneous eye blinks generate frequent potent interruptions to the retinal input and yet go unnoticed. As such, they provide an attractive approach to the study of the neural correlates of visual awareness. Here, we tested the potential role of predictability in generating blink-related effects using fMRI. While participants attentively watched still images of faces and houses, we monitored naturally occurring spontaneous blinks and introduced three kinds of matched visual interruptions: cued voluntary blink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A difference between the two is also found on a neural level. A higher activity in several visual areas have been reported for blanks, but not blinks Martin, 2000, 2002;Golan et al, 2018), and blinks (both voluntary and spontaneous) along with self-initiated blanks are associated with a decrease in activity in higher visual areas, whereas unpredictable external darkening causes an increase in higher-level areas (Golan et al, 2018). A difference in perceptual consequence following a blink vs. a blank is, therefore, not surprising.…”
Section: The Effect Of External Events: Blanks and Microshiftsmentioning
confidence: 88%
See 1 more Smart Citation
“…A difference between the two is also found on a neural level. A higher activity in several visual areas have been reported for blanks, but not blinks Martin, 2000, 2002;Golan et al, 2018), and blinks (both voluntary and spontaneous) along with self-initiated blanks are associated with a decrease in activity in higher visual areas, whereas unpredictable external darkening causes an increase in higher-level areas (Golan et al, 2018). A difference in perceptual consequence following a blink vs. a blank is, therefore, not surprising.…”
Section: The Effect Of External Events: Blanks and Microshiftsmentioning
confidence: 88%
“…With regard to the first question, one should bear in mind that even though blinks and blanks have a similar consequence on the retinal image, they are intrinsically different (Deubel et al, 2004;Higgins et al, 2009;Golan et al, 2018). Deubel et al (2004) found that adding a blank after a saccade can counteract the reduced detection of target displacement due to saccadic suppression, but a blink after a saccade does not have the same effect.…”
Section: The Effect Of External Events: Blanks and Microshiftsmentioning
confidence: 99%
“…These studies also supported a neural, rather than an optical, source of blink-related reduction in visual activity. In humans, functional MRI (fMRI) studies have provided further support for an extraretinal suppression in early visual regions during voluntary and spontaneous blinks, (Bristow, Haynes, Sylvester, Frith, & Rees, 2005; Golan, Grossman, Deouell, & Malach, 2018), and intracranial electroencephalogram recordings have revealed suppression of transient activity in the visual cortex during spontaneous and voluntary blinks (Golan et al, 2016).…”
mentioning
confidence: 99%
“…A difference between the two is also found on a neural level. A higher activity in several visual areas have been reported for blanks and not blinks (Gawne & Martin, 2000Golan et al, 2018) and blinks (both voluntary and spontaneous) along with self-initiated blanks are associated with a decrease in activity in higher visual areas; whereas unpredictable external darkening cause an increase in higher level areas (Golan et al, 2018). A difference in perceptual consequence following a blink vs a blank is therefore not surprising.…”
Section: The Effect Of External Events: Blanks and Microshiftsmentioning
confidence: 92%
“…With regard to the first question, one should bear in mind that even though blinks and blanks have a similar consequence on the retinal image, they are intrinsically different (Deubel et al, 2004;Golan et al, 2018;Higgins et al, 2009). Deubel et al (2004) found that adding a blank after a saccade can counteract the reduced detection of target displacement due to saccadic suppression, but a blink after a saccade does not have the same effect.…”
Section: The Effect Of External Events: Blanks and Microshiftsmentioning
confidence: 99%